The Association Between Impaired Awareness and Depression, Anxiety, and Apathy in Mild to Moderate Alzheimer's Disease: A Systematic Review - Azocar, Ignacia; Livingston, Gill; Huntley, Jonathan (Frontiers in Psychiatry, 2021)
Abstract Objectives. Impaired awareness of cognitive and functional deficits is a common feature of Alzheimer’s disease (AD). Although a lack of awareness has been suggested to be a protective factor against experiencing affective symptoms, such as depression, anxiety, and apathy which are common in AD, there is conflicting evidence about the links between them. This systematic review examines the evidence for an association between impaired awareness and depressive, anxiety, and apathy symptoms in mild to moderate AD. Method. We searched four databases (OvidMedline, Embase, PsychInfo, and PsychArticles) using terms encompassing awareness, apathy, depression, anxiety, and mild-moderate AD. We included studies that assessed the relationship between awareness and depressive symptoms, anxiety symptoms, or apathy. We assessed included papers for quality and report results using a narrative approach, prioritising high quality studies. Results. We identified 1544 articles, and twenty-seven studies fulfilled inclusion criteria (high-quality =15; moderate-quality =12). Most high-quality studies reported that impaired awareness in early-stage AD is cross-sectionally linked with fewer depressive symptoms and anxiety symptoms (correlation ranged from -0.3 to -0.7), but with more apathy. Conclusions. High-quality studies suggested that in people with early AD, impaired awareness is related to fewer depressive and anxiety symptoms and to more apathy. Future research should focus on elucidating causality among impaired awareness and these symptoms in AD.